Point-Symmetric Multivariate Density Function and Its Decomposition - Kiyotaka Iki; Sadao Tomizawa (Journal of Probability and Statistics)
For a T-variate density function, the present paper defines the point-symmetry, quasi-point-symmetry of order k (<T), and the marginal point-symmetry of order k and gives the theorem that the density function is T-variate point-symmetric if and only if it is quasi-point-symmetric and marginal point-symmetric of order k. The theorem is illustrated for the multivariate normal density function.